Analisis efisiensi pengeluaran pemerintah daerah sektor kesehatan di kabupaten/kota provinsi jawa tengah tahun 2015-2017 - Azmi, Fauzan (JURNAL DINAMIKA EKONOMI PEMBANGUNAN, 2020)
High amount on health spending in Central Java province has not been offset by the achievement of good health outcomes, mostly on the mortality rate. This study assess the relative efficiency, in terms of technical costs and technical health service system, and to know improvement target in order to achieve the efficiency in the 35 districts/cities of Central Java province in 2015-2017. This study uses Data Envelopment Analysis method, using health spending as input variables, facilities and health service as intermediate output variables, health outcomes as outcome variables, variable return to scale assumption and output orientation model. The results shows that the severity of inefficiency occurred at the cost technical efficiency, with only 2 districts/cities achieving perfect efficiency, while 4 districts/cities achieve perfect system technical efficiency. The districts/cities that sustain inefficiencies are need to improve through the calculation of improvement targets by optimizing the output.